The Economic Payoff of Name Americanization - Costanza Biavaschi; Corrado Giulietti; Zahra Siddique (Institute for the Study of Labor (IZA), 2013)
We examine the impact of the Americanization of names on the labor market outcomes of migrants. We construct a novel longitudinal data set of naturalization records in which we track a complete sample of migrants who naturalize by 1930. We find that migrants who Americanized their names experienced larger occupational upgrading. Some, such as those who changed to very popular American names like John or William, obtained gains in occupation-based earnings of at least 14%. We show that these estimates are causal effects by using an index of linguistic complexity based on Scrabble points as an instrumental variable that predicts name Americanization. We conclude that the tradeoff between individual identity and labor market success was present since the early making of modern America.
Keywords: J61; J62; Z1; N32; 330; Americanization; names; assimilation; migration